PENGARUH REKRUTMEN PEGAWAI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS HOTEL DAFAM PEKANBARU) - Saputra, Nurhadi; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to analyze employee recruitment and organizational commitment and its influence on employee performance at Hotel Dafam Pekanbaru. Employee Recruitment as a variable (X1), Organizational Commitment as a variable (X2), and Employee Performance as a variable (Y). The method used in this research is descriptive and quantitative using SPSS 21 program, where the sample used is 48 employees conducted by census and data collection technique through questionnaire. The result of analysis using validity test, test of reliability, test of determination, simple linear regression test, multiple linear regression test, t test and F test. So it can be concluded that employee recruitment has a significant influence on employee performance Dafam Hotel Pekanbaru, organizational commitment has significant influence on employee performance At Dafam Hotel Pekanbaru, and employee recruitment and organizational commitment have a significant influence on employee performance of Hotel Dafam Pekanbaru. Keywords: Employee Recruitment, Organizational Commitment and Employee Performance